Critical Understanding of culture and post-colonial awareness of problems.: Educational ethical perspectives (Pedagogical Horizons, 2021)
The following article is based on the question of what understanding of “culture” is used when speaking of “cultural differences” or “cultural conflicts” in an educational context. Empirical studies show that cultural-essentialist attributions and hegemonic imaginations can solidify the respective scope of action of affected individuals and, as a result, there are different opportunities for social participation and individual lifestyle. The everyday use of the term culture must be critically reflected on the background of the cultural turn and the emergence of anti-essentialist cultural concepts and sensitized for post-colonial problem awareness. The article advocates including theoretical considerations of postcolonialism as well as critical reflections on the concept of culture and on cultural theory in the educational context. In this way, essentialist external attributions and mechanisms of exclusion can be overcome.
Keywords: culture; cultural theories; cultural turn; postcolonialism; ethical education